4-1BB Signaling Promotes Alveolar Macrophages-Mediated Pro-Fibrotic Responses and Crystalline Silica-Induced Pulmonary Fibrosis in Mice - Lu, Yiping; Li, Chao; Du, Sitong; Chen, Xi; Zeng, Xinning; Liu, Fangwei; Chen, Ying; Chen, Jie (Frontiers in Immunology, 2018)
Silicosis is caused by exposure to crystalline silica (CS). We have previously shown that blocking 4-1BB signaling attenuated CS-induced inflammation and pulmonary fibrosis. However, the cells that express 4-1BB, which plays a vital role in promoting fibrosis, are still unknown. In this study, we demonstrated that the expression of 4-1BB is elevated in alveolar macrophages (AMs) in the lungs of CS-injured mice. CS exposure also markedly enhanced the expression of 4-1BB in macrophage-like, MH-S cells. In these cells, activation of the 4-1BB signaling with an agonist antibody led to up-regulated secretion of pro-fibrotic mediators. Consistently, blocking 4-1BB downstream signaling or genetic deleted 4-1BB alleviated pro-fibrotic responses in vitro, while treatment with a 4-1BB fusion protein promoted pro-fibrotic responses. In vivo experiments showed that blocking 4-1BB signaling decreased the expressions of pro-fibrotic mediators and fibrosis. These data suggest that 4-1BB signaling plays an important role in promoting AMs-mediated pro-fibrotic responses and pulmonary fibrosis. Our findings may provide a potential molecular target to reduce CS-induced fibrotic responses in occupational lung disease.